Euripides : Phoenician women. - Papadopolou, Thalia, 1971- (Bloombury Companions to Greek and Roman Tragedy, 2008)
"'Phoenician Women', one of Euripides' later tragedies, is an intriguing play that arguably displays some of his finest dramatic technique. Rich in cast and varied in incident, it is an example of Euripides' experimentation with structure. It dramatises the most fertile mythical tradition of the city of Thebes and its doomed royal family, focusing in particular on the conflict between Eteocles and Polyneices as a result of their father Oedipus' curse, which eventually leads to mutual fratricide. The play was very popular throughout antiquity, and became part of the so-called 'Byzantine Triad' (along with 'Hecuba' and 'Orestes'), of plays studied in the school curriculum. Thalia Papadopoulou here offers a thorough survey of the play in its historical context, against the background of Athenian tragedy and Euripidean dramaturgy. Employing various critical approaches, she investigates the literary tradition and the dynamics of intertextuality, Euripidean dramatic technique, the use of rhetoric, characterisation, gender, the function of the Chorus, aspects of performance and the reception of the play from antiquity to modern times."--Bloomsbury Publishing